Banking fintech adoption: systematic review with bibliometric and content analysis - Asif, Muhammad; Sarwar, Farhan; Lodhi, Rab Nawaz; Akbar, Rida (Serbian Journal of Management, 2024)
This study presents a comprehensive overview of the impact of Financial Technology (FinTech) on the banking sector, scrutinizing key trends and proposing future research directions to address the evolving challenges and opportunities in the field. Utilizing the PRISMA Flowchart, the study analyzes 93 papers on FinTech in banking published between 2016 and 2022 from the Web of Science database. Employing bibliometric and content analysis methodologies, RStudio, VOSviewer, and NVivo are used for descriptive, keyword co-occurrence, and content analyses, respectively. China leads in FinTech and banking research publications, while the United States surpasses all other nations in total citations. Word cloud charts and frequency analyses reveal that "Banks" and "FinTech" are frequently mentioned. The study identifies "Adoption," "Innovation," "Artificial Intelligence," and "Crowdfunding" as primary research topics. Emphasizing the global integration of blockchain, cloud computing, and big data into FinTech research, the study provides valuable insights into the possibilities and risks associated with technological advancements in the financial sector.
Keywords: FinTech; adoption; bibliometric analysis; SLR; innovation; VOSviewer